2017
DOI: 10.1155/2017/8098574
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Video Frame Size Distribution Originating from Scalable Video Codec (SVC)

Abstract: Designing an effective and high performance network requires an accurate characterization and modeling of network traffic. The modeling of video frame sizes is normally applied in simulation studies and mathematical analysis and generating streams for testing and compliance purposes. Besides, video traffic assumed as a major source of multimedia traffic in future heterogeneous network. Therefore, the statistical distribution of video data can be used as the inputs for performance modeling of networks. The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Finally, to simulate video feed processing, we define the size of each image frame using the distribution presented in [32] that found that the Pearson distributions are the best fit for the dataset used using both the graphical method and the hypothesis test.…”
Section: Benchmarks and Parameterizationmentioning
confidence: 99%
“…Finally, to simulate video feed processing, we define the size of each image frame using the distribution presented in [32] that found that the Pearson distributions are the best fit for the dataset used using both the graphical method and the hypothesis test.…”
Section: Benchmarks and Parameterizationmentioning
confidence: 99%
“…where F denotes the Fourier decomposition. Comparing (24) with (23), it indicates that the number is equivalent to the number of nonzero harmonic components in the Fourier series of , ( , ), in other words, is equal to the sum of nonzero number in ( ). After the determination of the -value, it is easy to achieve the weighting coefficient ( ), which is in fact the solution of the following equation by solving the Fourier transformation under the polar coordinates:…”
Section: Steerable Isotropic Gdf (Sigdf) the Isotropic Gkfbased Gdf Gmentioning
confidence: 99%
“…Since the visual appearance of a region in the imaged TP is determined by the random layouts of LHFs, the distinctive TP characteristics are inevitably related to the statistical methods [23]. The early widespread methods are the local or global statistics of the images pixel intensities or the image filter responses, such as the first-order and second-order statistics, and cooccurrence matrixes-based statistics, e.g., gray level cooccurrence or difference histograms [24], gray level cooccurrence matrix (GLCM), gray level run length matrix (GLRM) [25], and multivariate image analysis (MIA) [26], as well as their variants [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation